Comparison of Chest X-Ray of Pulmonary TB Patients with DM and Non DM at Anutapura Palu Hospital in 2020 - Nur Afni Fadillah; Ria Sulistiana; Fitriah Handayani (Jurnal EduHealth, 2023)
The incidence of Diabetes Mellitus (DM) in the world is rising particularly in developing countries where Pulmonary Tuberculosis (TB) is the most common. Diabetes Mellitus will increase the risk of Pulmonary Tuberculosis 1.5-7.8 times. The relationship between DM and TB has been proven that DM is a risk factor for TB. It affects the presence of Pulmonary Tuberculosis itself and the response to the treatment of Pulmonary Tuberculosis. Pulmonary Tuberculosis can cause glucose intolerance and worsen glycemic control in Diabetes Mellitus patients. Although Pulmonary Tuberculosis is more closely related to another immune-deficiency disease such as HIV, the number of people with diabetes is much greater. Therefore, DM is a more significant risk factor for the incidence of TB. Research Objective to find out the comparison of the characteristics of chest x- rays on Pulmonary Tuberculosis patients with Diabetes Mellitus and Non-Diabetes Mellitus at Anutapura Hospital in 2020. Research Method in this research applied an analytic observational study towards a cross sectional design. Sampling was selected through total sampling technique using inclusion and exclusion criteria. The research instrument was the patient's medical record. The results show that the most chest X-ray images on TB patients with DM are cavity images (53%) and TB patients with non-DM, the most features are fibrosis (35%). The result of the extensive description of the lesion indicatse that the extensive lesions is (15%) on TB patients with DM and (85%) on TB patients with non-DM and it is obtained that the minimal lesion is (1%) in both TB patients with DM and Non-DM. Research conclusion: There is no difference between chest X-Rays on Pulmonary Tuberculosis patients with Diabetes Mellitus and Non-Diabetes Mellitus.